2016
DOI: 10.1007/s00449-016-1546-4
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-synthesis of silver nanoparticles using Alternanthera tenella leaf extract: an effective inhibitor for the migration of human breast adenocarcinoma (MCF-7) cells

Abstract: In this study, phyto-synthesis of silver nanoparticles (AgNPs) was achieved using an aqueous leaf extract of Alternanthera tenella. The phytochemical screening results revealed that flavonoids are responsible for the AgNPs formation. The AgNPs were characterised using UV-visible spectrophotometer, field emission scanning microscopy/energy dispersive X-ray, transmission electron microscopy, fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction. The average size of the nanoparticles was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…However, some reports on the modified use of plant extracts have given insight into the possible organic moieties responsible for the metal ion reduction process along with greatly reducing the time duration for the synthesis [30,31,32,33]. The core-shell is nevertheless maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some reports on the modified use of plant extracts have given insight into the possible organic moieties responsible for the metal ion reduction process along with greatly reducing the time duration for the synthesis [30,31,32,33]. The core-shell is nevertheless maintained.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MNPs have gained special attention for their promising potential as anticancer agent [12,13,31,36,39,40,41,42]. Characteristics as their intrinsic cytotoxicity, their larger surface area, and area:volume ratio, their easily tunable surface that allow conjugation or encapsulation with biological targeting or therapeutic molecules, and their optical characteristics, make them optimal materials for cancer theranostics [39,43] which try to combine diagnosis and therapy into a single agent.…”
Section: Introductionmentioning
confidence: 99%
“…At present, limited information is available in the scientific literature regarding the use of a single substance from plant extract for the synthesis of MNPs. Recent reports in literature on this issue show that the flavonoids which have a wide existence in the plant extracts have a major contribution toward the bioreduction, capping, and stabilization of metal ions into NPs formation [28][29][30][31].…”
Section: Review Articlementioning
confidence: 99%
“…The detail of polyphenols and flavonoids employed in the synthesis of MNPs along with their biomedical efficacy is summarized in Table 2. Recently, it was reported that the major contribution for the synthesis of silver NPs (AgNPs) was of the total flavonoids present in the Alternanthera tenella and Coriandrum sativum leaf extracts [7]; and shown to be efficacious as antiacne, antidandruff, and anti-breast cancer agent as they were found active against Propionibacterium acnes, Malassezia furfur, and human breast adenocarcinoma cells, respectively [28,29].…”
Section: Polyphenols and Flavonoids-based Mnps And Their Biomedical Amentioning
confidence: 99%
“…Green nanotechnology or green synthesis is nothing but an organic synthesis of nanoparticles using plant extracts and the synthesized nanoparticles are then known as biogenic nanoparticles. In numerous studies huge number of medicinal plants are used to synthesize the silver NPs 74, 75 like Mulberry leaves 76 , Alternanthera dentate 77 , Ocimum sanctum 78 , Azadirachta indica 79 , Brassica rapa, Coccinia indica, Vitex negundo, Melia dubia are used have already been used to synthesize and stabilize metallic nanoparticles, very particularly biogenic silver (Ag) nanoparticles.…”
Section: Benefits Of Green Synthesis Silvermentioning
confidence: 99%